2023
DOI: 10.1088/1538-3873/acbe66
|View full text |Cite
|
Sign up to set email alerts
|

The Mid-infrared Instrument for JWST and Its In-flight Performance

Abstract: The Mid-Infrared Instrument (MIRI) extends the reach of the James Webb Space Telescope (JWST) to 28.5 μm. It provides subarcsecond-resolution imaging, high sensitivity coronagraphy, and spectroscopy at resolutions of λ/Δλ ∼ 100–3500, with the high-resolution mode employing an integral field unit to provide spatial data cubes. The resulting broad suite of capabilities will enable huge advances in studies over this wavelength range. This overview describes the history of acquiring this capability for JWST. It di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(58 citation statements)
references
References 50 publications
(35 reference statements)
0
47
0
Order By: Relevance
“…Recently, JWST/MIRI (Wright et al 2023) secondary eclipse measurements were used to provide the first observational constraints on whether or not the two innermost planets, TRAPPIST-1 b and c, had atmospheres (Greene et al 2023;Ih et al 2023;Zieba et al 2023). These studies complement previous efforts to use secondary eclipse measurements to probe atmospheric composition and thickness on hot rocky exoplanets (Kreidberg et al 2019;Crossfield et al 2022;Whittaker et al 2022).…”
Section: Introductionmentioning
confidence: 82%
“…Recently, JWST/MIRI (Wright et al 2023) secondary eclipse measurements were used to provide the first observational constraints on whether or not the two innermost planets, TRAPPIST-1 b and c, had atmospheres (Greene et al 2023;Ih et al 2023;Zieba et al 2023). These studies complement previous efforts to use secondary eclipse measurements to probe atmospheric composition and thickness on hot rocky exoplanets (Kreidberg et al 2019;Crossfield et al 2022;Whittaker et al 2022).…”
Section: Introductionmentioning
confidence: 82%
“…The complete details of the CEERS program will be presented in Finkelstein et al (2023, in preparation), and the program data can be found at doi:10.17909/z7p0-8481 and at https:// archive.stsci.edu/hlsp/ceers. This source is one of the first to be observed and published with four JWST (Gardner et al 2023) observing modes: NIRSpec (Böker et al 2023), NIRCam (Rieke et al 2023), MIRI (Wright et al 2023), and NIRCam/ Wide-Field Slitless Spectrograph, or WFSS (Greene et al 2017). We describe these observations below and provide a summary of information about this source in Table 1.…”
Section: Datamentioning
confidence: 99%
“…Owing to its proximity in the Large Magellanic Cloud (LMC), astronomers have been able to follow the evolution of this SN across the entire electromagnetic spectrum as it evolves into an SN remnant (SNR). The first JWST observations of SN 1987A were carried out as part of guaranteed time observation (GTO) program 1232 (PI: G. Wright), using NIRSpec (Jakobsen et al 2022) as well as the MIRI medium-resolution spectrometer (MRS; Wells et al 2015) and Imager (Bouchet et al 2015;Wright 2023). These observations provide unprecedented information about the IR emission from the system and make it possible to address a wide range of scientific questions regarding the ejecta, circumstellar medium (CSM), and compact object.…”
Section: Introductionmentioning
confidence: 99%